Scuba diving increases erythrocyte and plasma antioxidant defenses and spares NO without oxidative damage - Sureda, A.; Ferrer, M. D.; Batle, J. M.; Tauler, P.; Tur, J. A.; Pons, A. (Medicine & Science in Sports & Exercise, 2009)
Purpose: The aim of the present work was to study the effects of a single scuba diving immersion to high depth on erythrocyte and plasma antioxidant defenses, on erythrocyte cellular damage, and on nitric oxide (NO) production.